Análise do processo de degradação/desertificação na bacia do Riacho Feiticeiro, com base no DFC, município de Jaguaribe - Ceará - Pinheiro, Renata Aline Bezerra (2011)
This research discusses the problem of degradation / desertification in the in the Feiticeiro stream basin. With an area of 236 Km², is located northwest from the city of Jaguaribe, Ceara, inserted in the Jaguaribe river basin, which has a total area of 75.669 km ². This study was developed based in the methodology of physical conservationist diagnosis, with the aim of determining the potential for environmental degradation of the basin from the analysis of physical nature: climate index, rainfall erosivity, soil erodibility , average slope of the land, drainage density and index of vegetation cover. With the use of satellite images it was found the state of degradation of vegetation cover through the Normalized Difference Vegetation Index (NDVI). As the risks of anthropogenic desertification process are related to the type and intensity of use of natural resources and the consequences of that directly affect the population, there was a socioeconomic diagnosis from satellite images and data of agricultural production to analyze for use and occupation soil, as well as census data to analyze the population dynamics in relation to migration processes. The results may imply that there was an increase in vegetation cover, giving thus higher rates of protection in relation to risk of physical deterioration and degradation of vegetation. Also occurred between the years in question, the reduction of sites for agricultural use, deducing that there is indeed an indication of improvement in vegetation cover, which is consistent with the variation between different levels of environmental degradation / desertification. Thus, the environmental status of Feiticeiro Stream Basin needs further research to clarify the specific causes of this process of degradation / desertification, and actions to mitigate and combat the problem of desertification.